Juridical Analysis Among Special Confiscation At The Criminal Procedure Code And General Confiscation In Bankruptcy Law - Adhi Setyo Prabowo (Faculty of Law, Merdeka University Surabaya, Indonesia, 2020)
Bankruptcy means all matters relating to bankruptcy. Since the opinion of bankruptcy towards the debtor must go through a litigation process through the examination phase, everything related to the bankruptcy event is called bankruptcy. According to M. Hadi Shubhan, bankruptcy is a place where debtors are unable to make payments on creditors' debts. The management and empowerment of bankrupt assets are carried out by the curator under the supervision of a supervising judge with the main objective of the proceeds of the sale being to pay all debtor debt expenses proportionally and in accordance with the creditor structure. The curator is not the owner of bankruptcy property. Curators can only rely on creditors and debtors who meet the requirements and tidy up bankrupt assets for the benefit of creditors. Criminal law and civil law are two laws that often intersect or intersect, including in the bankruptcy compilation law the confiscation of assets belonging to the debtor. In carrying out their duties, curators are often confronted by police investigators or prosecutors compiling with confiscation of freedom over the portion of debtor's bankrupt assets. Conflicts between the interests of the police and the Attorney General's Office to carry out responsibility for the interests of the curator to conduct general confiscation of bankruptcy still frequently occur in the field. Article 39 paragraph (1) and paragraph (2) of the Criminal Procedure Code seized by investigators including objects that are in confiscation due to civil cases or bankruptcy can also be confiscated for the purposes of investigation, prosecution and trial of cases necessary. Article 39 Paragraph (2) of the Criminal Procedure Code gives the investigator legitimacy for confiscation of objects that have exceeded the general bankruptcy confiscation, as referred to in Article 39 paragraph (2) of the Criminal Procedure Code in conflict with Article 31 Paragraph (2) shall be made void and if requested by the Supervising Judge have to ask for a strike. This second article discusses clashes and difficulties in their application. One of the cases discussed was about general confiscation which was then confiscated by murder. Article 31 paragraph (2) of this UUK only covers in the realm of civil law and in accordance with the bankruptcy research event can be confiscated because of bankruptcy due to the pronouncement of bankruptcy by the judge, then all confiscation of bankrupt assets becomes invalid again. Article 39 Paragraph (2) of the Criminal Code states that objects in a bankruptcy case can be confiscated by investigators for the purpose of investigating, prosecuting and prosecuting court cases, therefore confiscation in legal proceedings must take precedence.